SANSKRITIC PURĀṆIC SOURCES AND THE TAMIL MYTHIC LEGENDS IN THE CAṄKAM LITERATURE ‘KALITTOKAI’: English - K., Kesava Rajarajan; S, Sivagurunathan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The classical phase of Tamil literature, which lasted from the second century BCE to the fifth century CE, includes a vast corpus that is divided into the Pattuppāṭṭu and Eṭṭuttokai, including the Tolkāppiyam. The Kalittokai is similar to the Paripāṭal, the 150 poems deal with the different landscapes and phases of love poems, it may be understood that the mythologies of the pan-Indian order and the typical Tamil idioms have gone a long way in the making of a cosmopolitan picture. The Tamils had no inhibition in taking from others and shared their ideas with others. In certain cases, the pan-Indian myths were altered to suit the Tamil taste, e.g., ‘Dharma’ is a pan-Indian remoulded to suit Tamil culture. Thus, the Tamil and Sanskritic mythological and legendary ideas have moved like the warp and woof in ancient Tamil literature. References to the Sanskritic sources of events are ample, and at the same time, no events in the Indian Epics are discernible. The semblance between the narratives of Kalittokai and Cilappatikāram may suggest a date of proximity to the epic. It all depends on where we fix the Cilappatikāram and Maṇimēkalai. Several layers of poems may be found in the Kalittokai, as is the case with Puṟam 400 and Akam 400. The earlier stratum may return to the BCEs and the later stratum around 400 CE. In an ocean of love poems, sources relating to the pan-Indian purāṇas are scattered sporadically. The Sanskritic sources and ideas had been systematically merged into the Tamil cultural heritage, and influence had an enormous upshot on the ancient Tamil literature. These show how the Āryan ideas had intermingled with the thought of the Tamils. Besides, it shows how Indian culture is an admixture of Tamil and Sanskrit ideas from very early times, starting with Tolkāppiyam.